Competitive Advantage and Bank Value: State-Owned Compared to Private Banks - Lintang Edityastono; Kusairi Kusairi; Rachma Bhakti Utami (Universitas Negeri Semarang, 2025)
This study research aims to test and analyze the effect of Competitive Advantage on bank value while comparing the value of state-owned and private banks in Indonesia. Competitive Advantage is essential for banking because it helps banks differentiate themselves from competitors and create unique value for stakeholders, and it is reflected through factors or attributes that make a bank superior to its competitors. The independent variable in this study is Competitive Advantage, measured through capital requirements and product differentiation, while the dependent variable is bank value, measured through the market-to-book ratio and Tobin’s Q. This study used 328 financial reports from 41 sample banks in Indonesia, with data obtained from annual reports and financial statements published on the companies’ websites from 2015 to 2022. The data were analyzed using the PLS-SEM approach, while comparisons between state-owned and private banks were conducted using PLS-Multigroup analysis with the assistance of WarpPLS software. The results show that Competitive Advantage has a significant positive effect on bank value in both state-owned and private banks. Furthermore, the type of bank has not been proven to moderate the effect of Competitive Advantage on bank value.